Factors Causing Delays in Road Construction Projects in Kerinci Regency - Junata, Hengki; Jumas, Dwifitra Y; Rita, Eva (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Delays in road construction projects are one of the problems that often occur in the implementation of infrastructure development, especially in Kerinci Regency. This study aims to identify and analyze the factors causing delays in road construction projects in the region. The research method used is quantitative descriptive with a survey approach. The study population consisted of contractors, project supervisors, and related parties involved in the implementation of road projects, with samples taken purposively. The data collection instrument is in the form of a questionnaire that is compiled based on indicators of project delay factors, such as project management, human resources, equipment, weather conditions, and funding. The data obtained was analyzed using descriptive statistics to determine the frequency, percentage, and ranking of factors that contributed to project delays. The results show that project management and planning factors are the main causes of delays, followed by limited human resources and equipment, as well as unfavorable weather conditions. These findings provide a comprehensive overview of the obstacles faced in road construction projects in Kerinci Regency and can be used as a reference for related parties to design mitigation strategies to increase the effectiveness and timeliness of project implementation.